Cephalometric Evaluation of Molar Distalization by a Compact RPE Screw Combined with a Modified Nance Appliance - Mazen Al Masry; Toros Alcan; Cenk Ceylanoğlu (Galenos Yayinevi, 2005)
The aim of this study is to evaluate the effects and results of a newly designed intra-oral molar distalization device. The study involves 8 (1 male and 7 females) patients with class II dental relationship. The mean age of the patients was 14.1. Molar distalization was achieved by intermittent forces, where the compact RPE screw is placed in mesiodistal direction between molars and premolars. After the completion of distalization, the appliance was kept in mouth passively for 3 months for retention purpose. Patients were instructed to turn the screw 1 time a week (meaning 1/4 turn each week) and activation continued until super class one dental relationship was achieved. The status will be retained with the same screw, kept in position, for approximately 3 months. Lateral cephalometric radiographs were taken at the day of insertion of the device (before opening the screw), and at the end of treatment. Tracing of these radiographs gave us a detailed view of the result of our study and the effectiveness of the new device. The significant changes achieved were as follows: The upper first molars were distalized in an average of 2.68 mm, tipped 2.62° distally. The upper central incisors were proclined by an average of 2.5 mm and tipped 4.9° labially. IMPA increased 1.09°, the lower molars extruded 1mm, and overjet increased 1,3mm. On the other hand, there were no significant skeletal changes.